Knowledge, attitude, and practice towards volunteerism: a perspective from Sultan Idris Education University - Jamal, Mohamad Basri; Sarifin, Muhammad Ridhwan; Hamzah, Intan Suria (Journal of Education and Learning (EduLearn), 2025)
Volunteering requires a high level of commitment to community development, especially from young people. The first study aimed to assess the knowledge, attitude and practices of university students of education regarding volunteering and the second study, analysing the differences in students’ knowledge regarding interest in volunteering. The survey method using Google form was distributed among the students of volunteer course semester 2 2022/2023 at Sultan Idris Education University. A total of 459 respondents provided the feedback. Overall, students’ knowledge about the volunteer course was excellent. Their attitudes towards volunteering activities tend to undertake activities related to their interests in terms of the types of volunteers available. Encouraging things in volunteering practice shows that students keep learning things related to volunteering, keep looking for opportunities to help others, and influence others to do it together. The analysis of students’ knowledge related to volunteering among students by interest showed that there was a significant difference in the mean of students’ knowledge by interest, where respondents’ interest in volunteering for the community was much higher than in other volunteering activities. Further studies should be conducted to better understand volunteerism among high school students who are now immersed in technology.